Chemical composition and in vitro bioactivity of essential oil obtained from the flavedo of 'Pompia', an ancient Sardinian fruit. Issue 5 (3rd September 2019) - Rosa, Antonella; Nieddu, Mariella; Petretto, Giacomo Luigi; Sarais, Giorgia
ABSTRACT: Pompia ( Citrus limon var. pompia ) grows in the North-East Sardinia (Italy). This fruit is used in traditional pastries, the flavedo for the preparation of liqueurs by hydroalcoholic infusion. We investigated the chemical composition and bioactivity of the essential oil obtained by hydro-distillation from the peel of pompia (PEO). Gas chromatographic analysis allowed us to determine the PEO chemical composition: the major compound was limonene (LM) (803.8 mg/mL). PEO showed antioxidant activity in the β-carotene/linoleic acid bleaching test and radical-scavenging activity in the DPPH assay. PEO significantly reduced viability in HeLa and B16F10 cancer cells, and its toxic effect was mainly associated with LM cytotoxicity. PEO significantly increased intracellular free radical levels in cancer cells, without affecting the cellular phospholipid composition. The HPLC-DAD analysis of the cancer cell medium after PEO-treatment revealed the presence of perillic acid, a LM metabolite with anticancer activity. Our findings provide new insights for the PEO nutraceutical potential.